THE RETIREMENT CONSUMPTION PUZZLE: EVIDENCES FOR BRAZIL AND THE STATE OF RIO GRANDE DO SUL - Stampe, Marianne Zwilling; Porsse, Alexandre Alves; Portugal, Marcelo Savino; Zuanazzi, Pedro Tonon (Análise Econômica, 2017)
The life cycle/permanent income theories predict that consumption would be constant over time but such result has been challenged by some empirical studies which show a systemic decrease in consumption at retirement. This paper aims to investigate the so-called retirement consumption puzzle for Brazil and the State of Rio Grande do Sul. We estimated consumption functions controlling age effects for 12 composite goods using information from the 2008-2009 Household Budget Survey. The results showed that households’ expenditures systematic decrease with age for 7 composite goods (food, clothing, transport, hygiene, education, recreation and miscellaneous) and increase with age for 2 composite good (health care and housing). The patterns found to the households’ expenditures by age structure brings evidence of retirement consumption puzzle in Brazil.